2020
DOI: 10.3390/ijerph17061929
|View full text |Cite
|
Sign up to set email alerts
|

An Anecdotal Case Report of Chronic Lymphatic Leukemia with del(11q) Treated with Ibrutinib: Artificial Nourishment and Physical Activity Program

Abstract: Chronic lymphatic leukemia (CLL) is the most frequent type of leukemia in western countries and when association with del(11q) is correlated with a worse prognosis. We reported the clinical case of an 80-year-old patient with CLL related to del(11q) and a BMI of 16.4 kg/m2, who presented a voluminous mass in abdominal cavity (23 × 14 × 4 cm) which occupied the whole of the mesentery and the retroperitoneal space, treated with ibrutinib, adequate nutrition, and a program of physical activity. He showed a great … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The study showed that patients with hematologic cancers had a similar rate of SARS‐CoV‐2 infection as that of health care providers, but, once infected, they presented a more serious disease and a significantly higher mortality rate 5 . These example data, together with the data from few small other studies, suggest that the exposure of patients with cancer to SARS‐CoV‐2 is very risky, and that every possible precaution must be put in place to prevent this from happening 6‐12 . These considerations also apply to the context of bone marrow transplantation 13‐15…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The study showed that patients with hematologic cancers had a similar rate of SARS‐CoV‐2 infection as that of health care providers, but, once infected, they presented a more serious disease and a significantly higher mortality rate 5 . These example data, together with the data from few small other studies, suggest that the exposure of patients with cancer to SARS‐CoV‐2 is very risky, and that every possible precaution must be put in place to prevent this from happening 6‐12 . These considerations also apply to the context of bone marrow transplantation 13‐15…”
Section: Introductionmentioning
confidence: 95%
“…5 These example data, together with the data from few small other studies, suggest that the exposure of patients with cancer to SARS-CoV-2 is very risky, and that every possible precaution must be put in place to prevent this from happening. [6][7][8][9][10][11][12] These considerations also apply to the context of bone marrow transplantation. [13][14][15] We have prepared this review article for all doctors who have not had the opportunity to investigate the different aspects of COVID-19 sufficiently, including young infectious disease specialists, hematologists, and general practitioners, who for more than one reason may meet patients with COVID-19, having to make a first diagnosis and the first decisions about it.…”
mentioning
confidence: 99%
“…After two relapses, our patient achieved complete remission of the disease with brentuximab used as a third-line therapy. According to international guidelines, patients with ALCL ALK +, once a CR at a rescue therapy has been obtained, must undergo allo-SCT, which could have a high chance of success [ 31 , 32 , 33 , 34 , 35 ]. The young age of the patient and her refractory to the first- and second-line treatments prompted us to proceed toward allo-SCT, so far without success, due to the unsuitability of the contacted donors [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This effect is further strengthened by the expression of MYC (“double-expresser” lymphoma; DE) and by the translocations of both the MYC and BCL2 genes (double-stroke lymphoma). This has been the most coveted therapeutic targets for all B-cell cancers until venetoclax, the first selective inhibitor of the BCL2, has been marketed [5, 6]. This drug is administered orally and has indications in the USA, Europe, and some other countries to treat adults with chronic lymphatic leukaemia, with or without 17p deletion, who have failed at least 1 previous treatment.…”
Section: Introductionmentioning
confidence: 99%